2019
DOI: 10.3390/su12010021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monitoring and Analysis of Ecological Quality of Pingtan Comprehensive Experimental Zone, a New Type of Sea Island City, Based on RSEI

Abstract: Islands face increasingly prominent environmental problems with rapid urbanization. Hence, timely and objective monitoring and evaluation of island ecology is of great significance. This study took the Pingtan Comprehensive Experimental Zone (PZ) in the east sea of Fujian Province of China as the research object. Based on remote sensing technology, four Landsat images from 2007 to 2017 and the remote sensing ecological index (RSEI) were used to explore the ecological status and space-time change. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 32 publications
(31 reference statements)
2
28
0
Order By: Relevance
“…EEQ assessment is a useful tool to help decision-makers fully understand the natural and anthropogenic effects on the regional eco-environment and provide them with valuable information to formulate corresponding measures [7]. Till now, numerous researches have been conducted to evaluate the regional ecoenvironment at various scales, such as farmland [8], province [6], [9] prefecture-level city [10], urban agglomeration [5], river basin [7], [11], island [12], open pits [13], and tableland [14]. However, based on existing studies, it can be found that few studies have performed at the urban agglomeration scale.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…EEQ assessment is a useful tool to help decision-makers fully understand the natural and anthropogenic effects on the regional eco-environment and provide them with valuable information to formulate corresponding measures [7]. Till now, numerous researches have been conducted to evaluate the regional ecoenvironment at various scales, such as farmland [8], province [6], [9] prefecture-level city [10], urban agglomeration [5], river basin [7], [11], island [12], open pits [13], and tableland [14]. However, based on existing studies, it can be found that few studies have performed at the urban agglomeration scale.…”
Section: Introductionmentioning
confidence: 99%
“…Under such background, integrating with remote sensing datasets and geographical information system technology to evaluate the regional ecoenvironment has attracted the attention of scholars all over the world [19]. Currently, remote sensing with its advantages of rapid, real-time, and large-scale monitoring has made much progress in land use classification [20]- [23], eco-environment evaluation [12]. For example, the normalized difference vegetation index (NDVI) has been widely used to monitor the regional vegetation situation [24]; the land surface temperature (LST) retrieved from thermal images is applied to evaluate the urban heat island [25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations